PSYCHOEDUCATION PROGRAM FOR MOTHER IN ACCOMPANYING CHILDREN LEARNING AT HOME IN RISKY SITUATION - MUHAMAD YULIAN RISMA PRATAM; Alifah Indalika Mulyadi Razak (SEAMEO CECCEP, 2021)
The health emergency situation the spread of the Covid-19 virus that has swept across the world has changed almost a large part of the education system, one of which also has an impact on the level of early education which requires children to study at home. The difference in learning needs and children's development is a challenge for mothers as a significant other child, to continue to meet household needs to fulfill children's learning needs while at home. The psychoeducation program is one of the solutions in providing information and assistance in providing knowledge to mothers when accompanying children to study at home in emergency situations, as the main objective of this study. The process of implementing a psychoeducation program for mothers uses a variety of model information assistance with stages (1) experiencing; (2) reflecting; (3) problem solving; and (4) problem questioning, which was implemented through 10 interventions consisting of 5 times the delivery of psychoeducation information and 5 times assistance in the form of personal counseling, namely mentoring individually to 30 research participants to listen to problems, obstacles, constraints and provide solutions to the problems faced, especially in measuring 40 indicator items consisting of aspects (1) sense of parenting, measuring the mother's knowledge of the importance of positive care from an early age; (2) a sense of learning, which measures the mother's knowledge of children's learning needs; and (3) a sense of risky situation, which measures the mother's knowledge of handling health emergency situations. The research design used one group pretest posttest experimental design, which tested the level of knowledge of the research sample before and after being given an intervention in the form of an educational program. The results show that there is a difference in the mean test of maternal knowledge after receiving a psychoeducation program (Mpre test = 122.033 <Mpost test = 142.7), the effectiveness of the psychoeducation program is considered significant (Sig. (2-tailed)) = 0.000 (<α = 0.05) has an influence on the knowledge of mothers in accompanying children to study at home in emergency situations.